Formation of a Tourism Entrepreneurial Environment in the Conditions of Competition - BIRYUKOV, Vladimir Aleksandrovich; DMITRIEVA, Olga Vladimirovna; FROLOVA, Victoria Borisovna; NIKANDROVA, Larisa Konstantinovna; ARKHIPOV, Andrey Borisovich (Journal of Environmental Management and Tourism; Vol 10 No 8 (2019): JEMT Volume X Issue 8(40) Winter 2019, 2020)
The article is devoted to the formation of a tourism entrepreneurial environment in the conditions of competition. It has been established that the tourism industry, although positioned at the state level as a priority sector for the development of the national economy, is not being developed enough. One of the reasons for this situation is the lack of understanding by government representatives of the importance of tourism as an industry and not just as a form of leisure activity. It has been proved that the tourism industry needs to move to a qualitatively new level of development where strategic management is the basis for such development, around which all tourism activities and their management are formed – regular advertising campaigns, long-term development programs, systematic participation in various world tourism forums and other events.